Tunisia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Tunisia's Request for Purchase Under the Rapid Financing Instrument (RFI). The IMF financing will support the authorities' emergency measures to contain the spread of the virus and mitigate its human, social, and economic toll amid unprecedented uncertainty. These measures involve raising health spending, strengthening social safety nets, and supporting small- and medium-sized firms hit by the crisis. The RFI is the most appropriate instrument to help address the urgent balance of payments need considering that too little time would have been left before the Extended Fund Facility expiration on May 19 to agree on the significant revisions to program objectives required in response to the Covid-19 shock. The IMF financing will also ensure an adequate level of international reserves and catalyze additional donor financing. The authorities are committed to maintaining prudent economic policies and resuming fiscal consolidation once the crisis abates to ensure macroeconomic stability and the sustainability of Tunisia's debt. Macroeconomic stability and debt sustainability hinge on strong policy and reform implementation. The authorities are committed to resuming fiscal consolidation once the crisis abates.